2002
DOI: 10.1081/erc-120016826
|View full text |Cite
|
Sign up to set email alerts
|

Baboon Cyp11b1: The Localization and Catalytic Activity in Baboon Adrenal Tissue

Abstract: A third gene encoding baboon CYP11B1 was isolated and was shown to catalyze only the metabolism of deoxycorticosterone (DOC) to corticosterone. The investigation into the localization of CYP11B1 in the baboon adrenal tissue, using in situ hybridization, showed that mRNA transcripts were predominantly present in the zona reticularis (ZR) and zona fasciculata (ZF). Signal was also observed in the zona glomerulosa (ZG) and scattered within the medulla. Immunohistochemical studies, using rabbit anti-sheep CYP11B1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…27 There are a few reports suggesting the existence of these enzymes in the adrenal medulla. 28,29 Murrell et al 27 reported that PC12 cells expressed d5,3b-hydroxysteroid dehydrogenase isomerase mRNA, as determined by quantitative polymerase chain reaction, which further supports the possible production of cardenolides and bufadienolides in the adrenal medulla and PC12 cells. We reported that a substance with OL-IR was secreted from PC12 cells and that the addition of progesterone to the culture increased OL-IR content.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…27 There are a few reports suggesting the existence of these enzymes in the adrenal medulla. 28,29 Murrell et al 27 reported that PC12 cells expressed d5,3b-hydroxysteroid dehydrogenase isomerase mRNA, as determined by quantitative polymerase chain reaction, which further supports the possible production of cardenolides and bufadienolides in the adrenal medulla and PC12 cells. We reported that a substance with OL-IR was secreted from PC12 cells and that the addition of progesterone to the culture increased OL-IR content.…”
Section: Discussionmentioning
confidence: 86%
“…The adrenal cortex is the main tissue for steroidogenesis and the adrenal medulla requires 11β‐hydroxysteroid dehydrogenase 26 and δ5,3β‐hydroxysteroid dehydrogenase for steroidogenesis to occur 27 . There are a few reports suggesting the existence of these enzymes in the adrenal medulla 28,29 . Murrell et al.…”
Section: Discussionmentioning
confidence: 99%